Pelaksanaan Perceraian Pada Masyarakat Muslim Di Pulau Kecil (Studi Kasus Desa Pulau Kampai Kecamatan Pangkalan Susu) - Muhammad Hasbi; Muhammad Saleh; Azhar (Journal Smart Law, 2023)
Marriage According To Law No. 1 Of 1974 Is An Inner And Outer Bond Between A Man And A Woman As Husband And Wife With The Aim Of Forming A Happy And Eternal Family (Household) Based On Belief In One And Only God. However, In Carrying Out These Ideals, Sometimes A Household Experiences Problems That End In Separation Or Divorce. Then, As A Form Of Upholding Justice For The Indonesian People In Terms Of Implementing Divorce, The Government Has Determined That The Implementation Of Divorce Recognized By The State Is Through A Court Process. Even Though Government Regulations Have Stipulated This, For The Muslim Community In The Small Island Area, The Implementation Of Divorce Is Sometimes Not In Accordance With Existing Regulations, Because Of The Lack Of Transportation Facilities And The Condition Of The Area That Is Far From The Location Of The Judiciary And Also Because Of The Limited Economic Conditions Of The Community. In Addition To This, The Public's Understanding Of The Legality Of Religious Divorce Without Going Through A Judicial Process Has Become One Of The Factors That Has Led To Many Muslim Communities In Small Islands Only Seeing This Regulation As Merely An Administrative Order. Then For The Sake Of Creating Justice For Society And Also Because Of The Importance Of Orderly Administration Of The Status Of Each Resident, There Needs To Be Attention And The Best Solution From All Existing Stakeholders, Be It The Government, Religious Leaders Or The Community Itself.